"A consagração de um sonho: O culminar da última etapa" - Marcos Eloi Barros Pereira (2021)
This document corresponds to the professional internship report that specifies the path of an intern teacher, the author, over a school year full of mistakes, difficulties, but above all, a full of learning. This report aims to obtain a Master's degree in Physical Education Teaching in Basic and Secondary Education at the Faculty of Sport of the University of Porto. Despite all the skills and knowledge that I gained from the 1st year's teorethical classes, it was in the Professional Internship that I was forced to put all this knoledge to test and confront it with the real context of practice. This supervised teaching practice made me start to develop my professional identity, through the various situations experienced, the difficulties felt, the mistakes made and also the sharing of experiences and perspectives. The professional internship took place at the Rodrigues de Freitas Basic and Secondary School, in Porto, always with the follow-up, support and supervision of a cooperating teacher from the school institution, and under the guidance, counseling and constant help of the faculty advisor. This was a very unusual year, taking into account the current pandemic situation, and this report also portrays this stage of professional internship under the added constraints that the pandemic brought. A year full of adversities and uncertainties, but one that made me take full advantage of the internship. KEYWORDS: